Impact of milk supply schemes on the economy in milk collection areas of Delhi milk scheme - Jain, J. P. (Indian Agricultural Statistics Research Institute, 1978)
Surveys done in the milk-shed areas of the Delhi Milk Scheme during 1966-1967 and 1972-1973, and in the Dudhsagar Dairy, Mehsana, Gujarat, during 1966-1967 and 1973-1974.